Good looking bridges Cavendish Conference Centre, London, Monday 22 November 1993 (Thomas Telford, 1993)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present.
Keywords: Bridges -- Design and construction -- Congresses.; elektronické knihy; electronic books